2023
DOI: 10.1098/rsob.220377
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative single molecule analysis of podoplanin clustering in fibroblastic reticular cells uncovers CD44 function

Abstract: Upon initial immune challenge, dendritic cells (DCs) migrate to lymph nodes and interact with fibroblastic reticular cells (FRCs) via C-type lectin-like receptor 2 (CLEC-2). CLEC-2 binds to the membrane glycoprotein podoplanin (PDPN) on FRCs, inhibiting actomyosin contractility through the FRC network and permitting lymph node expansion. The hyaluronic acid receptor CD44 is known to be required for FRCs to respond to DCs but the mechanism of action is not fully elucidated. Here, we use DNA-PAINT, a quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…During embryogenesis, PDPN is essential for the heart and lymphatic system formation [88][89][90][91][92][93] . In adult life, PDPN is physiologically expressed by Lymphatic Endothelial Cells (LECs) and Fibroblastic Reticular Cells (FRCs) in lymph nodes and allows immune cells to adhere to LECs and FRC to facilitate migration and antigen presentation [94][95][96] After MI, PDPN acts as an inflammatory marker and newly acquired PDPN by MSC help them to interact and communicate with recruited and activated immune cells CD11b high which highly express the PDPN receptor named C-type lectin-like receptor 2, CLEC-2 19 . The interaction between PDPN and CLEC-2 activates an inflammatory response in immune cells 97,98 , and we recently showed that blocking the interaction between MSC positive for PDPN (MSC PDPN+ ) and macrophages improved cardiac function and scar composition after infarction 17,97,98 .…”
Section: Podoplanin a Possible Mesenchymal Stromal Cells Inflammatory...mentioning
confidence: 99%
See 1 more Smart Citation
“…During embryogenesis, PDPN is essential for the heart and lymphatic system formation [88][89][90][91][92][93] . In adult life, PDPN is physiologically expressed by Lymphatic Endothelial Cells (LECs) and Fibroblastic Reticular Cells (FRCs) in lymph nodes and allows immune cells to adhere to LECs and FRC to facilitate migration and antigen presentation [94][95][96] After MI, PDPN acts as an inflammatory marker and newly acquired PDPN by MSC help them to interact and communicate with recruited and activated immune cells CD11b high which highly express the PDPN receptor named C-type lectin-like receptor 2, CLEC-2 19 . The interaction between PDPN and CLEC-2 activates an inflammatory response in immune cells 97,98 , and we recently showed that blocking the interaction between MSC positive for PDPN (MSC PDPN+ ) and macrophages improved cardiac function and scar composition after infarction 17,97,98 .…”
Section: Podoplanin a Possible Mesenchymal Stromal Cells Inflammatory...mentioning
confidence: 99%
“…Myocardial infarction and heart failure [16][17][18]103,104 Mesenchymal stromal cells Cardiac Fibrosis 56,94,105 Mesenchymal stromal cells and early reactive fibroblasts Thrombi and thrombo-inflammation 97,106 Mesenchymal stromal cells Deep vein thrombosis 19,107 Mesenchymal stromal cells Atherosclerotic lesion 23,[108][109][110] Mesenchymal stromal cells, Smooth muscle cells and macrophages Aneurysm and High arteria shear 85,111 Mesenchymal stromal cells Calcification aortic valves 112 Mesenchymal stromal cells and fibroblast…”
Section: Source Of Fundingmentioning
confidence: 99%